2015
DOI: 10.1049/iet-map.2014.0365
|View full text |Cite
|
Sign up to set email alerts
|

Planar antennas for compact multiband transceivers using a microstrip feedline and multiple open‐ended ground slots

Abstract: Two planar antennas for compact multiband transceivers are presented, that employ an open-ended microstrip feedline that couples to multiple open-ended ground slots. The effect of separately introducing each of the slots on the antenna performance is outlined, and it is shown that the resonant frequencies of the antennas can be independently controlled by adjusting the dimensions of the ground slots. Antenna 1, consisting of an open-ended microstrip feedline that couples to three open-ended ground slots, exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…From the distributions, it is observed that the resonance is generated by the high-order mode and radiates from the open slot too. Although not shown here for brevity, the U-shaped feeding line is also responsible for some radiation, especially at high frequencies, which is demonstrated in [36].…”
Section: Antenna Analysismentioning
confidence: 96%
“…From the distributions, it is observed that the resonance is generated by the high-order mode and radiates from the open slot too. Although not shown here for brevity, the U-shaped feeding line is also responsible for some radiation, especially at high frequencies, which is demonstrated in [36].…”
Section: Antenna Analysismentioning
confidence: 96%
“…Rapid development of cutting-edge technologies (e.g., 5G [1], internet of things [2], or wearable devices [3], including those for tele-medicine purposes [4]), leads to increasingly exacting requirements imposed on contemporary antenna structures. Among these, demands for miniaturization [5], multi-functionality [6], or multi-band operation [7] can be listed. In consequence, the complexity of the antenna geometries grows steadily, along with the number of design variables required for their parameterization.…”
Section: Introductionmentioning
confidence: 99%
“…Many types of antennas appropriate for multiband WLAN/WiMAX applications have been reported recently . To sum it up, the main design approaches fall into three categories.…”
Section: Introductionmentioning
confidence: 99%
“…The first method is most convenient, which usually makes modifications on the radiating patch or the ground plane of the antenna. In , a planar antenna for compact multiband transceivers covering the standards of WiMAX, HiperLAN, and WLAN is presented. The resonant frequencies can be independently adjusted by the open‐ended ground slots.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation